ANALYSIS OF FACTORS AFFECTING INTEREST TO BUY CONSUMERS ON USE OF E-COMMERCE IN THE ERA OF COVID-19 PANDEMIC (A Case Study of STIE Wijaya Mulya Students Surakarta) - Tetyaranisa Kartika; Edi Purwanto; Santosa Tri Prabawa (ITB AAS Indonesia Surakarta, 2022)
This study aims to determine the variables of Lifestyle (X1), Perceived Behavioral Control (X2), and Motivation (X3) that affect Consumer Buying Interest (Y) towards the use of e-commerce in the era of the covid-19 pandemic. This study used multiple linear regression which was analyzed using IBM SPSS 25 software, while the results of the regression equation obtained were Y = 3.310 + 0.248 X1 + 0.105 X2 + 0.551 X3 + e. The data used is primary data using the entire population with the number of respondents as many as sixty-six students of STIE Wijaya Mulya Surakarta class of 2020/2021 Accounting and Management study program. The findings indicate that the Lifestyle variable (X1) tcount (2.526) > ttable (1.55), the hypothesis is accepted, which means that there is a partially significant effect on Consumer Buying Interest (Y). Perceived Behavioral Control (X2) tcount (1.133) < ttable (1.55), the hypothesis is rejected, which means that there is no partially significant effect on Consumer Buying Interest (Y). Motivation (X3) tcount (4.899) > ttable (1.55), the hypothesis is accepted, which means that there is a partially significant effect on Consumer Buying Interest (Y) on the use of e-commerce in the era of the covid-19 pandemic. The results of the F test obtained Fcount (20.946) > Ftable (9.3), the hypothesis is rejected, which means that there is a simultaneous significant effect of Lifestyle (X1), Perceived Behavioral Control (X2), and Motivation (X3) variables on Consumer Buying Interest (Y). Of the three independent variables the most dominant is Motivation (X3) where the value of tcount is (4,899) > ttable (1,55), meaning that the hypothesis is proven true. From the Coefficient of Determination test (R2), the results are 0.503 (50.3 %), proving that the variable of Consumer Buying Interest (Y) is influenced by Lifestyle (X1), Perceived Behavioral Control (X2), and Motivation (X3) variables. influenced by other factors. Keywords : Lifestyle (X1), Perceived Behavioral Control (X2), Motivation (X3), and Consumer Buying Interest (Y)